Simultaneous Spectrophotometric Determination of Zinc, Cadmium and Lead by Xylenol Orange Using the Partial Least Squares Method After Their Preconcentration by 5,10,15,20-Tetrakis(4-Carboxylphenyl)porphyrin on Amberlite IRA-402 Resin - Saber Tehrani, Mohammad; B. Ghasemi, Jahan; Taghi Baharifard, Mohammad (Asian Journal of Chemistry, 2012)
A new solid phase extraction method for separation and preconcentration of trace amounts of zinc, cadmium and lead in water samples is proposed. The procedure is based on the adsorption of complexes of Pb, Cd and Zn with 5,10,15,20-tetrakis(4-carboxylphenyl)porphyrin (TCPP) on anionic Amberlite IRA-402 resin prior to their simultaneous spectrophotometric determination with xylenol orange, using partial least squares method. The enrichment factor for preconcentration of zinc, cadmium and lead was found to be 10. The precision of the method, evaluated as the relative standard deviation obtained by analyzing a series of 10 replicates, was below 4 % for Pb, Cd and Zn. A selective method for group separation of Pb, Cd and Zn in the presence of interfering ions was applied. The practical applicability of the developed method was examined using synthetic natural waters and alloy samples.